Impacto moderador do capital social na relação entre nível socioeconômico e qualidade de vida relacionada à saúde bucal de gestantes - Pacheco, Sabrina Cabral (2023)
Pregnancy is an important moment in life, where women experience major physiological, psychological and behavioral changes, making them more vulnerable to problems in their general health. In addition, for more prone women, these alterations may favor the occurrence of adverse oral conditions and affect the Oral Health Related Quality of Life (OHRQoL). In addition to oral clinical conditions, psychosocial factors have been gaining prominence in the literature as predictors of oral health. In this context, social capital (SC) stands out, which is conceptualized as conditions invested and produced by relationships and social networks and their meaning for individuals and groups; and can be classified as individual SC and contextual SC. In this context, the aim of this study was to evaluate the effect that the individual social capital has on the relationship between family income and OHRQoL of pregnant women in the municipality of Santa Maria, Rio Grande do Sul. This study has had a cross sectional design and sociodemographic, economic, psychosocial and behavioral data were collected using structured questionnaires. The Oral Health Impact Profile questionnaire (OHIP-14) was used to assess OHRQoL. SCwas assessed using the adapted version of the S-ASCAT. Trained and calibrated examiners assessed the clinical conditions. In addition to the descriptive analysis, multilevel Poisson regression models were used to assess the moderating effect of SC on the relationship between family income and OHRQoL. Results: 520 pregnant women were evaluated (93% response rate). Both SC dimensions showed a moderating effect on the relationship between income and OHRQoL. Among the participants with low family income, those without social support and who do not attend the pregnant women's group, had, respectively, 44% [RR 1.44 (95% CI 1.22-1.72)] and 22% [RR 1.22 (95% CI 1.05-1.42)] a more negative impact on OHRQoL than their counterparties. Conclusion: Our findings showed that the lack of both SC dimensions intensified the association of low income and low OHRQoL among pregnant women. It suggests that the presence of cognitive and structural SC could act as a protective factor inadverse socioeconomic conditions.